Research on direct shear test of rock-like materials with two closed pre-existing cracks of different attitudes - Yue, Ling; Niu, Jie; Ma, Qingshan; Zhao, Chengxi; Cao, Minjun; Yu, Bangyong (Frontiers in Earth Science, 2023)
To investigate the failure mode and strength characteristics of rock-like materials containing two non-coplanar closed discontinues, and the influence of crack attitude on the shear failure of rock mass, a series of direct shear tests are carried out on rock-like materials containing two pre-existing cracks of different attitudes, one of them is horizontal crack, and the other is inclined crack. The specimens containing pre-existing cracks of four inclinations (0°, 45°, 135°, and 180°) and three dip angles (30°, 60°, and 90°) are prepared, and the failure form and stress-displacement curve are recorded during the tests. The results show that the attitude of the crack has a significant effect on the failure form and strength characteristics. In positive shear, the shear stress increases slowly and the crack initiation of the crack occurs relatively late, and in negative shear, the shear stress increases rapidly and the crack initiation stage appears earlier. Under the normal stress of 1 MPa, the fracture surface fluctuates along the pre-existing cracks, and the difference in shear strength of each specimen is less than 1.0 MPa. Under the normal stress of 5 MPa, the fracture surface mostly distributes along the horizontal direction, and the difference in shear strength of each specimen is about 2.0 MPa. Under the same level of normal stress, the crack initiation and peak stress vary with the attitude of pre-existing crack, and the variation trend of peak stress is changed when the normal stress increased due to the difference in failure form. It is calculated that the ratio of crack initiation stress to peak stress ranges from 0.61 to 0.80.